Model zplyňování biomasy - Studený, Vojtěch (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Matematické modely zplyňování jsou vhodné pro predikci složení plynu a jeho vlastnosti. Cílem diplomové práce je sestavit matematický model pro zplyňování biomasy. První část práce se věnuje popisu zplyňování a užívaným technologiím. Součástí teoretické části je rešerše způsobů modelování. Další část se věnuje popisu modelu a rovnic, které jsou jeho součástí. Součást zadání je parametrická studie, která znázorňuje změny produkce plynu a jeho vlastnosti při změně daných parametrů. Na závěr je model porovnán s daty získanými při experimentu na fluidním reaktoru biofluid 2.

Mathematical models of gasification are suitable for predicting gas composition and its properties. The aim of the diploma thesis is to compile a mathematical model for biomass gasification. The first part deals with the description of gasification and the technologies used. Theoretical part consists of the search of modeling methods. Other theoretical part is devoted to the description of the model and equations presented in the thesis. Part of the assignment is a parametric study that shows changes in gas production and its properties when changing the parameters. Finally, the model is compared with the data obtained in the experiment on the fluid reactor biofluid 2.
Biomass gasification model
Keywords: zplyňování; biomasa; matematický model; energoplyn; parametrická studie; gasification; biomass; mathematical model; energy gas; parametric study